Euro area private consumption: Is there a role for housing wealth effects - Frauke Skudelny (European Central Bank (ECB), 2009)
This paper adds to the literature on wealth effects on consumption by disentangling financial wealth effects from housing wealth effects for the euro area. We use two macro-datasets for our estimations, one on the aggregate euro area for the period 1980-2006, and one on the individual euro area countries from1995-2006, using panel data techniques. The impact of all wealth variables on euro area consumption is significant and positive in most specifications for both datasets. The marginal propensity to consume (MPC) out of financial wealth is roughly in line with the literature, with 2.4 to 3.6 cents per euro of financial wealth spent on consumption according to the estimations with euro area aggregate data. However, the panel estimation yields somewhat lower results (0.6 to 1.1 cents). The MPC out of nominal housing wealth lies between 0.7 to 0.9 cents per euro for both datasets. When specifying housing wealth in real terms, i.e. when taking out the effect of volatile house prices, we find similar effects in the times series estimation while the MPC is larger in the panel estimation (2.5 cents).
Keywords: E21; 330; Consumption; euro area; financial wealth; housing wealth; Vermögenseffekt; Konsumentenverhalten; Immobilienpreis; Börsenkurs; Panel; Eurozone; EU-Staaten